Unusual case of antiphospholipid syndrome presenting as adrenal insufficiency. Issue 3 (17th March 2020) - Warriach, Sanval Ahmed; Mustafa, Mohamad; O'Keeffe, Denis; Watts, Michael
Abstract : A 64-year-old man presented to the emergency department with generalised fatigue and dizzy spells. His background history includes a previous admission with right leg deep vein thrombosis, provoked by pneumonia. Laboratory results showed evidence of hyponatremia and hyperkalaemia. A synacthen test was performed that indicated hypoadrenalism. CT of his abdomen revealed enlarged adrenal glands bilaterally. Adrenal antibodies and positron emission tomography (PET) scan were performed to assess the cause of enlarged adrenals. PET scan showed no evidence of increased uptake. Adrenal antibodies were found to be negative. Tuberculous (TB) adrenalitis was the principle differential diagnosis. TB QuantiFERON was strongly positive. Following 9 months of TB treatment, surveillance CT scan indicated a significant reduction in adrenal gland size. However, subsequent events culminated in a retrospective review of CT scans questioning the initial clinical diagnosis and suggesting that the observed adrenal gland enlargement was secondary to bilateral adrenal infarction and haemorrhage. Equally, the subsequently observed marked reduction in adrenal gland size was not secondary to an assumed response to TB therapy, but rather the sequela of infracted atrophied adrenal glands, as a manifestation of the underlying antiphospholipid syndrome (APS). The case highlights the importance of recognising adrenal insufficiency in patients with a history of APS. It also illustrates the role of multidisciplinary meetings in the management of such complex cases.